Pemanfaatan Media Sosial Sebagai Strategi Pemasaran Dalam Meningkatkan Volume Penjualan Pada Layanan Perjalanan Pariwisata “Abrisam Tour” - Dessy Purnama Sari; Sutrisno Sutrisno; Rauly Sijabat (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
Currently, MSMEs can use social media as a way to market their goods so that consumers know more about their goods. MSMEs that have online access, engage in social media, and develop e-commerce will usually enjoy significant business benefits in terms of revenue, innovation, and competitiveness. This research uses a qualitative descriptive research method, research informants use purposive sampling, data collection techniques through observation, interviews and documentation, triangulation techniques using time triangulation. Oki Candra Mentari said that after the Covid-19 pandemic, Abrisam Tour Travel Bureau started using social media as a marketing strategy. However, due to the lack of post promotion on social media, this strategy has not been effective. Abrisam Tour uses a strategy that starts by trying to provide professional service to its customers so that they feel satisfied and enjoy their services. This strategy is used through social media, namely WhatsApp and WhatsApp Status and Instagram, to target Outing Class customers, both those who have used Abrisam Tour services before and those who have not. Abrisam Tour strives to provide the best experience to customers by offering high-quality tour packages, adequate facilities and professional services. In addition, Abrisam Tour seeks to increase brand awareness and attract more customers through advertising and branding on social media such as WhatsApp and Instagram.